TRADISI SEDEKAH BUBUR DI PASAR TERUSAN KABUPATEN BATANG HARI SEBAGAI MANIFESTASI SYUKUR DAN NILAI RELIGI DALAM BUDAYA LOKAL - Khairunnisa, Rani; Dini Putri Zahara; Yuliana Damayanti; Tihan Arvita; Luvita Anggraini; Philsa Arin Pateka; Gress Vinessa Simorangkir; Mei Nurcahyanti; Mia Apta Candra; Aurora Karina Tomia Putri; Abiy Dzaki Edison (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study addresses the challenges of maintaining local traditions amidst modernization, focusing on the Porridge Almsgiving tradition in Terusan Market. The research aims to describe the practice and analyze the religious values embedded as a manifestation of community gratitude before the rice harvest. A qualitative methodology using a literature review was employed, drawing data from scientific journals, news articles, and relevant books. The results indicate that this generational tradition, involving seven hamlets, is performed during the rice growth phase as a spiritual effort to seek blessings and safety. The community interprets the ritual as an expression of gratitude to God, fostering social solidarity through values of sincerity and togetherness. Despite modernization, the tradition persists through strong local government support and strategic revitalization efforts, such as integrating the tradition into educational institutions through creative dance performances.